Development of a tool for management, monitoring and control of water supply systems - Gonzalez Agudelo, Jeronimo (2020)
In current days, a large part of the water supply companies performs the pumping operation in an empirical was without taking into account factors such as the electric tariff, the efficiency of the pump, and water availability, having large operating costs. This work aims to propose and validate a methodology that includes the monitoring, manage and control stages of the water supply systems reducing the operational and energy-relates costs. The monitoring stage includes the use of an instrumentation support system that gathers information of the water system such as flow rates, water tank levels and pipe pressure. The monitoring system is also used to forecast water demands. The management stage is responsible to find the pump operation schedule in order to reduce energy costs. In this work, the water system is modelled through 3 methods: (a) an empirical method developed by the author; (b) using water flow balance equations and (c) using the hydraulic simulator EPANET. The optimum pump operational schedule is found using a binary genetic algorithm. The methodology was implemented using python code. The results obtained show that the methodology developed and implemented lead to a reduction in pumping energy-costs and can be used for the control stage. This work was done with the collaboration of the SCUBIC company.